Potential therapeutic effects of apigenin for colorectal adenocarcinoma: A systematic review and meta‐analysis - Koohyar Ahmadzadeh; Shayan Roshdi Dizaji; Fatemeh Ramezani; Farnad Imani; Jebreil Shamseddin; Arash Sarveazad; Mahmoud Yousefifard (Cancer Medicine)
Abstract Purpose Therapeutic management of colorectal cancer (CRC) does not yet yield promising long‐term results. Therefore, there is a need for further investigation of possible therapeutic options. Various experiments have studied the effects of apigenin on CRC and have shown conflicting results. This systematic review and meta‐analysis investigates the currently existing evidence on the effect of apigenin on CRC. Methods Medline, Embase, Scopus, and Web of Science databases were searched for articles related to apigenin and its effect on CRC in the preclinical setting. Cell viability, growth inhibition, apoptosis, and cell cycle arrest for in‐vitro, and body weight, tumor size, and mortality in in‐vivo studies were extracted as outcomes. Results Thirty‐nine articles investigating colorectal adenocarcinoma were included in this meta‐analysis. Thirty‐seven of these studies had data for in vitro experiments, with eight studies having data for in vivo experiments. Six articles had both in vitro and in vivo assessments. Our analysis showed apigenin reduces cell viability and induces growth inhibition, apoptosis, and cell cycle arrest in in vitro studies. The few in vivo studies indicate that apigenin decreases tumor size while showing no effects on the body weight of animal colorectal adenocarcinoma models. Conclusion Our results demonstrated that apigenin, through reducing cell viability, inducing growth inhibition, apoptosis, and cell cycle arrest, and also by decreasing the tumor size, can be considered as a possible adjuvant agent in the management of colorectal adenocarcinoma. However, further in vivo studies are needed before any efforts to translate the current evidence into clinical studies.